The Household Livelihood Structures and Strategies of Beef Cattle Breeders Around Oil Palm Plantations in Watubangga Kolaka - Suparman Suparman; Kartomo Kartomo; Muhammad Obi Kasmin; Nursalam Nursalam; Muhtar Amin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The expansion of oil palm plantation areas has also created a new zoning system that restricts village communities' freedom to reach areas once used as farming and livestock locations. This study aims to analyze income and expenditure, analyze the structure of household livelihoods, and determine the strategies for fulfilling household livelihoods of beef cattle farmers in oil palm plantation areas in Watubangga, Kolaka. Respondents in this study amounted to 35 farmer households determined by a simple random sampling method. The primary and secondary data were used. Data analysis used in this research includes income, saving capacity, and descriptive analysis. The results showed that the average income of cattle farmer households in Watubangga Subdistrict, Kolaka Regency, was IDR 18,918,750 per month, with an average household expenditure of IDR 6,506,250 per month and an average saving capacity of IDR 12,412,500 per month. Household livelihood strategies applied in Watubangga, Kolaka, are spatial engineering (migration), farming livelihood engineering, and dual livelihood patterns. This study can be followed up with a study on the welfare level of the farming community to find out how the structure and livelihood strategies fulfill the welfare of the farming community.